Pengaruh Pemberian Snack Puding Dadih Susu Kerbau dan Edamame Terhadap Kadar Glukosa Darah Puasa dan Profil Lipid pada Pasien Diabetes Mellitus: Pengaruh Pemberian Snack Puding Dadih Susu Kerbau dan Edamame terhadap Kadar Glukosa Darah Puasa dan Profil Lipid pada Pasien Diabetes Mellitus - Liri Sisca Wulandari; Inggita Kusumastuty; Anggun Rindang Cempaka; Fajar Ari Nugroho (Amerta Nutrition, 2023)
Background: Buffalo milk curd, a native probiotic source from Indonesia, is dominated by live indigenous Lactic Acid Bacteria known for their ability to lower blood glucose levels. Edamame contains amino acid arginine, chromium, antioxidants, and fibre, aiding in blood glucose control and lipid profile reduction. Objectives: This study aimed to assess the effects of buffalo milk curd and edamame-based pudding snacks on fasting blood glucose levels and lipid profiles in Type 2 diabetes mellitus (T2DM) patients. Methods: This study used a True Experiment Design with Pretest-Posttest Control Group Design. The study involved 32 patients divided into treatment and control groups. During the study, the treatment group received 250 g of snacks in the morning and evening for one week. Blood glucose levels and lipid profiles were measured using the enzymatic colourimetry method. Results: The results showed decreased fasting blood glucose levels before and after treatment in both control (-17.06 ± 40.17) and treatment (-48.38 ± 40.27 mg/dl) groups (p=0.036). Total cholesterol levels also decreased in control (-15.87 ± 23) and treatment (-41.4 ± 19 mg/dl) groups (p=0.001). There were decreased LDL levels in control (-6.81 ± 29.09) and treatment (-27.3 ± 25.09 mg/dl) groups (p=0.04). However, HDL and TG levels showed no differences at the end of the study. Conclusions: Buffalo curd milk-edamame pudding snacks can reduce fasting blood glucose levels and lipid profiles, particularly total cholesterol and LDL levels, in Type 2 DM patients.